2015
DOI: 10.4103/0975-9476.146543
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive activity of Astragalus gummifer gum (gum tragacanth) through the adrenergic system: A in vivo study in mice

Abstract: Background:In Iranian traditional medicine, gum obtained from Astragalus gummifer and some other species of Astragalus was used as analgesic agent.Objective:In this study, we investigated the antinociceptive effect of several concentrations (125, 250, and 500 μg/kg body weight) of Astragalus gummifer gum (AGG) on thermal and acetic acid induced pain in mice.Materials and Methods:AGG was dissolved in distillated water and injected i.p to male mice 15 minute before the onset of experiment. Writhing and hot-plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The doses of ketoprofen, opioid, muscarinic, nicotinic, and adrenergic receptor agonists and antagonists were determined by previous studies, which identified the maximum dose that did not affect motor function [24,25,26,27,28,29]. …”
Section: Methodsmentioning
confidence: 99%
“…The doses of ketoprofen, opioid, muscarinic, nicotinic, and adrenergic receptor agonists and antagonists were determined by previous studies, which identified the maximum dose that did not affect motor function [24,25,26,27,28,29]. …”
Section: Methodsmentioning
confidence: 99%
“…It has also shown that the presence of phenolic and flavonoid compounds were associated with antiinflammatory and antinociceptive activity of other species of asparagus. The hydroalcoholic extract of A. radix (Maresca et al, 2017), A. pubescens (Nwafor and Okwuasaba, 2003) and A. hamosus (Shojaii et al, 2015), as well as the gum of A. gummifer (Bagheri et al, 2015) exerted a significant antinociceptive activity.…”
Section: Asparagus Officinalis L (Asparagus) Frommentioning
confidence: 99%
“…In comparison with other groups, there were differences but not significant between the group treated with apigenin (27.2±4.11) and diclofenac (23.8±3.36), which recorded the lowest number of writhing values (Table 2). To evluate the central and peripheral influnces of analgesics in mice, the writing test employs a chemical technique involving intraperitoneal administration of acetic acid to induce pain (Bagheri et al, 2015;Fattollah et al, 2023). The analgesic activity indicated a reduction in frequency.…”
Section: Acetic Acid Testmentioning
confidence: 99%